2006
DOI: 10.1152/ajpheart.00772.2006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of reactive oxygen species generation after opening of mitochondrial KATP channels

Abstract: OPENING of the ATP-sensitive K ϩ (K ATP ) channel mediates the cardioprotective effect induced by pathophysiological stressors such as ischemic preconditioning (IPC) (15,29), heat shock (19), and pharmacological agents, including adenosine (5), ACh (26), opioids (12), monophosphoryl lipid A (31), phosphodiesterase 5A (PDE5A) inhibitors (24,27), and mTOR inhibitor, rapamycin (20). In addition, direct opening of the mitochondrial K ATP (mitoK ATP ) channels with diazoxide induces early and delayed preconditionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…While sildenafil has been shown to exert antioxidant effects in some experimental systems [30,31], pro-oxidant effects of sildenafil have also been reported in monocytes and tumor cells [32,33]. Although the mechanism by which sildenafil stimulates oxidative stress is not known, a mitochondrial pathway has been proposed [34]. Consistent with this notion, we found that sildenafil stimulates mitochondrial superoxide production in vascular SMCs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…While sildenafil has been shown to exert antioxidant effects in some experimental systems [30,31], pro-oxidant effects of sildenafil have also been reported in monocytes and tumor cells [32,33]. Although the mechanism by which sildenafil stimulates oxidative stress is not known, a mitochondrial pathway has been proposed [34]. Consistent with this notion, we found that sildenafil stimulates mitochondrial superoxide production in vascular SMCs.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, the sildenafil-mediated increase in HO-1 expression is blocked by the mitochondrial electron transport chain complex I inhibitor rotenone, further implicating this organelle with the induction of HO-1 by sildenafil. The mechanism by which sildenafil activates Nrf2 is unclear but it likely involves the oxidation of cysteine residues in Keap1 since several cysteine residues undergo redox-dependent alterations that result in the release and/or blockade of Keap1-dependent ubiquitination and catabolism of Nrf2 [23,34]. Indeed, we found that N-acetyl-L-cysteine inhibits the expression of Nrf2 by sildenafil.…”
Section: Discussionmentioning
confidence: 91%
“…339 The molecular identity of mitochondrial K ATP channels is not clear in detail, but there seems to be a multiprotein complex consisting of a sulphonylurea receptor and a potassium channel unit; 340-342 the potassium channel unit was recently characterized in detail and shares homology with the renal outer medullary potassium channel. 343 The mitochondrial K ATP channel is a target of NO, 344 PKC, 167,[345][346][347][348][349] and PKG 350 and on its activation releases ROS which, in turn, activate the PKCε in a positive feedback loop. 184,351 There is also a close interaction of mitochondrial K ATP with mitochondrial Cx 43 in the release of ROS.…”
Section: Mitochondrial Permeability Transition Porementioning
confidence: 99%
“…4 Various steps of the contractile process have proven to be susceptible to redox modulation. First, the probability of isolated sarcoplasmic reticulum (SR) calcium ion release channels opening increases upon oxidation of accessible protein thiols.…”
Section: Introductionmentioning
confidence: 99%